2017
DOI: 10.1021/acssensors.7b00103
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Self-Assembled Aptamer and Newly Designed Zwitterionic Peptide as Antifouling Biosensing Interface for Electrochemical Detection of alpha-Fetoprotein

Abstract: A sensitive and low-fouling aptasensor for alpha-fetoprotein (AFP) was developed based on mixed self-assembled aptamers and newly designed zwitterionic peptides, where densely immobilized peptides formed an antifouling layer to resist nonspecific protein adsorption, and sparsely attached aptamers acted as the recognizing layer to achieve target binding. The obtained biosensing interface responded to the target AFP with a strikingly selective and sensitive manner, exhibited excellent protein-resistant performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(75 citation statements)
references
References 30 publications
0
74
0
1
Order By: Relevance
“…Peptides are prospective candidates among antifouling materials because, apart from their ease design and synthesis, they are composed of natural amino acids which are zwitterionic molecules in biological systems and, therefore, possess inherently outstanding biocompatibility [36]. Besides superior biocompatibility and coordination ability, particularly designed peptides with strong hydrophilicity and neutral charge [37,38,39] help to prevent nonspecific protein adsorption through hydrophobic interaction and charge attraction, respectively [5,6].…”
Section: Antibiofouling Peptides and Peptoid-based Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Peptides are prospective candidates among antifouling materials because, apart from their ease design and synthesis, they are composed of natural amino acids which are zwitterionic molecules in biological systems and, therefore, possess inherently outstanding biocompatibility [36]. Besides superior biocompatibility and coordination ability, particularly designed peptides with strong hydrophilicity and neutral charge [37,38,39] help to prevent nonspecific protein adsorption through hydrophobic interaction and charge attraction, respectively [5,6].…”
Section: Antibiofouling Peptides and Peptoid-based Materialsmentioning
confidence: 99%
“…Cui et al [6] reported a low-fouling aptasensor for the determination of alpha-fetoprotein (AFP) using mixed self-assembled aptamers and newly designed zwitterionic peptides. The long-chained AFP-specific aptamers acted as the recognizing layer and the designed short-chained zwitterionic peptides (with good hydrophilicity, nearly electrical neutrality) endowed biocompatibility and antifouling ability against nonspecific protein adsorption.…”
Section: Antibiofouling Peptides and Peptoid-based Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these are considered as the “gold standard” materials, they show various defects such as their oxidative damage, poor water-solubility, and low protein resistance at high temperature. Peptides have come up as possible alternative antifouling materials in electrochemical affinity biosensors [ 30 , 31 , 32 ], providing additional advantages of biocompatibility, tunable and simple structure and synthesis [ 24 ].…”
Section: Continuous Real-time Electrochemical Biosensors: Towardsmentioning
confidence: 99%